Transazioni, solidarietà, umanitarismo - Roberto Malighetti (EtnoAntropologia, 2014)
The paper introduces the session by integrating the different contributions in the common effort to analyze ethnographically the configurations of humanitarian aid and of the international cooperation and in combining the institutional analysis with the study of the ideologies, the projects, the discourses and the practices. It also invites to interpret the articles as ways to understand how the activities of the subaltern groups may offer important contributions in the elaboration of new forms of citizenship and of new rights.